GA Based Selective Harmonic Elimination for Multilevel Inverter with Reduced Number of Switches: An Experimental Study - Bektas, Enes; Karaca, Hulusi (Elektronika ir Elektrotechnika, 2019)
In power electronic applications, especially high power and medium voltage, multilevel inverters (MLIs) have been commonly used. MLIs ensure high quality load voltage and lower Total Harmonic Distortion (THD) than traditional inverter. In this paper, a multilevel inverter structure with reduced number of power switches is proposed. The proposed multilevel inverter is lower costed than conventional MLI. Also, a Genetic Algorithm (GA) based Selective Harmonic Elimination (SHE) technique has been used for the first time in the proposed MLI structure with reduced number of switches. The proposed GA based SHE technique computes the optimum switching angles by solving nonlinear harmonic equations of multilevel inverter. Both Isochronous switching (IS) and SHE techniques have been applied to proposed MLI to demonstrate the effectiveness of the GA based SHE technique. Simulation and experimental results for 7, 11 and 13-level have been obtained. Results of 11-level inverter is analysed and given in detail. Results have clearly proved that desired order harmonics in proposed MLI topology can be eliminated by using GA based SHE technique and lower THD on the load voltage has been provided.